OVERVIEW OF QbD: A CHALLENGE TO THE PHARMACEUTICAL INDUSTRY - Narke, Ramakant M; Singh, R. P. (Asian Journal of Pharmaceutical Research and Development, 2014)
QbD (Quality by design) is a holistic approach where product specifications, manufacturing process and critical parameters are included in order to ease the final approval and ongoing quality control of new drug. QbD is based upon the ICH Q9 [Quality Risk Management] and Q8 [Pharmaceutical Development]. Also the ultimate objective of this approach is to promote faster and more consistent product and process development activities, and to increase manufacturing flexibility and process robustness in order to reduce production costs. Thus product quality is monitored throughout its development and hence it is an important factor. Similarly, QbD is important in pharmaceutical industry as quality matters in each and every step for the production of the drug. In this review, overall QbD along with its principles and the steps responsible for the implementation of QbD are discussed. Also major steps in the process for the implementation of QbD in Pharmaceutical Industry the pros and cons of QbD with industrial examples are discussed here. Various tools of QbD are been discussed here with a 7 step plan process for QbD. Similarly PAT (Process Analytical Technology) is an important aspect of QbD which is discussed here. QbD is a promising idea which offers pharmaceutical manufacturer with increased self-regulated flexibility while maintaining firm quality standards and real time release of the drug product.